METHODOLOGY OF TEACHING RUSSIAN LANGUAGE AND LITERATURE (Ta'limning zamonaviy transformatsiyasi, 2024)
The methodology of teaching Russian language begins with teaching language to elementary school students. The first method of teaching Russian language is practical technique. Psychological and pedagogical regularities of the learning process are similar to the needs of society. At the heart of these needs are the means of communication. Communication tools determine the ways of teaching students Russian language according to their linguistic characteristics. The methodology of teaching Russian language consists of literary parts, language skills of students, concepts of grammar, changes in the language system over time (assimilation) and other parts of language science.